2006
DOI: 10.1016/j.pain.2005.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of focal small-fiber axonal degeneration in complex regional pain syndrome-I (reflex sympathetic dystrophy)

Abstract: CRPS-I consists of post-traumatic limb pain and autonomic abnormalities that continue despite apparent healing of inciting injuries. The cause of symptoms is unknown and objective findings are few, making diagnosis and treatment controversial, and research difficult. We tested the hypotheses that CRPS-I is caused by persistent minimal distal nerve injury (MDNI), specifically distal degeneration of small-diameter axons. These subserve pain and autonomic function. We studied 18 adults with IASP-defined CRPS-I af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
187
0
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(209 citation statements)
references
References 37 publications
11
187
0
11
Order By: Relevance
“…For example, a loss of IENF like that reported here for paclitaxel-and vincristineevoked pain has been documented in the neuropathic pain syndromes that accompany diabetes and glucose intolerance (Sumner et al, 2003), post-herpetic neuralgia (Oaklander, 2001), complex regional pain syndrome type-I (Albrecht et al, 2006;Oaklander et al, 2006), and burning mouth syndrome (Lauria et al, 2005b). We are still unable to identify the neural lesion that accompanies the painful peripheral neuropathy produced by ddC, but doses of ddC that are larger than those we tested do produce an anatomical lesion (Keswani et al, 2003).…”
Section: Functional Consequences Of Ienf Losssupporting
confidence: 62%
“…For example, a loss of IENF like that reported here for paclitaxel-and vincristineevoked pain has been documented in the neuropathic pain syndromes that accompany diabetes and glucose intolerance (Sumner et al, 2003), post-herpetic neuralgia (Oaklander, 2001), complex regional pain syndrome type-I (Albrecht et al, 2006;Oaklander et al, 2006), and burning mouth syndrome (Lauria et al, 2005b). We are still unable to identify the neural lesion that accompanies the painful peripheral neuropathy produced by ddC, but doses of ddC that are larger than those we tested do produce an anatomical lesion (Keswani et al, 2003).…”
Section: Functional Consequences Of Ienf Losssupporting
confidence: 62%
“…Early concerns that CRPS was caused by psychopathology were resolved by pathological demonstration of somatotopic dysfunction and degeneration of small unmyelinated axons (Fig. 3) [42][43][44], and epidemiological studies finding no association with psychopathology [45,46]. As CRPS resolves, which it usually does even without treatment [47], the edema, temperature changes, hyperhidrosis, and abnormal hair growth usually resolve before the pain [48,49], so late-stage patients often no longer meet diagnostic criteria for CRPS but only for posttraumatic neuralgia, demonstrating that these are on a continuum (Fig.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…On the other hand, other researchers have suggested that CRPS type 1 is neuropathic pain based on direct evidence of nerve injury. Oaklander et al demonstrated loss of axons in the CRPS-affected limb by means of skin biopsy, indicating hypoesthesia of CRPS-affected limbs; and Blaes et al reported autoantibodies to the surface of peripheral autonomic neurons in sera from CRPS type 1 patients, which produced sympathetic dysfunction in CRPS-affected limbs [13,14]. Thus, the controversy as to whether CRPS type 1 is primarily neuropathic or nociceptive has raged for more than two decades.…”
Section: Discussionmentioning
confidence: 99%